Influence Play Collage With Grain Media To Ability Motor Smooth Children Aged 4-5 Years At PAUD Atika Regency Takalar - Nurrisda; A. Sri Wahyuni Asti; Parwoto (Institut Pendidikan Alfatah Mataram, 2026)
This research aims to determine fine motor skills using collage play at the age of 5-6 years in early childhood . This research aims to determine fine motor skills using play games at the age of 5-6 years in early childhood. The research approach used is a quantitative approach with a Quasi Experimental Design research type. The population in this study was 14 children. The sample in this study consisted of 14 children, divided into 7 children as the experimental group and 7 children as the control group. The data analysis techniques used are descriptive statistical analysis and non-parametric analysis. The fine motor skills of children for the experimental group showed that it was -2.401 and the sig (2-tailed) value was 0.041 < 0.05, so it can be concluded that there is a difference in the fine motor skills of children in the experimental group before and after being given treatment. Based on the research results, it can be concluded that the fine motor skills of children who were treated with grain collage in the experimental group were better than the control group. So, it can be concluded that grain collage has a significant influence on the fine motor skills of children aged 5-6 years in PAUD Atira, Takalar Regency.